(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
A cross-sectional study was carried out among 110 mothers of children to assess the immunization status of the children, they selected by using non probability sampling (convenience sampling). According to study findings, most of children were males (25.7%) and (95.5%) of them from urban resident and most of children have a good immunization status. The study concluded that performance of Iraqi national immunization program is effective Keywords: Immunization Status, Children Under 6 Years Old.